Akal dan Wahyu dalam Persfektif Muhammad Iqbal - Nasir, Muhammad (Medan Resource Center, 2022)
The issue of reason and revelation has long been discussed by theological schools in Islam. Conversations related to reason and revelation did not take place only in the 20th century AD. Theseissues are still being discussed, including Muhammad Iqbal who was one of the Islamic reformers. He was born on 9 November 1877 in Sialkot which is a region of Punjab, Pakistan anddied on 19 April 1938 at the age of 60. The utilization of reason is a manifestation of faith because with this utilization man will avoid backwardness, decline, and even man will become advanced in mastering this realm. With regard to the issue of revelation, Iqbal stated that revelation is an expectation and an inner experience. God in this inner espktasi reveals Himself to man who goes on a spiritual journey.